2009
DOI: 10.1016/j.metabol.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean diet is favorably associated with metabolic parameters in HIV-positive patients with the highly active antiretroviral therapy–induced metabolic syndrome and lipodystrophy

Abstract: Objective-To investigate whether closer adherence to a Mediterranean dietary pattern is associated with metabolic aspects of the Highly Active Antiretroviral Therapy (HAART)-induced metabolic syndrome (fat redistribution, insulin resistance, dyslipidemia) in HIV positive patients. Design-Cross sectional study.Methods-227 HIV-infected patients were evaluated during a single outpatient visit to the General Clinical Research Center of Beth Israel Deaconess Medical Center. Usual dietary intake and physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 30 publications
0
27
0
7
Order By: Relevance
“…They observed a positive association between kilocalories from sweets intake and higher insulin resistance as measured by the homeostatic model assessment of insulin resistance (HOMA-IR). [42] Investigations with self-reported dietary intake that evaluated the Mediterranean dietary pattern with biomarker profiles for diabetes and cardiovascular disease risk present equivocal results,[4345] while an upcoming study will directly measure the impact of a Mediterranean diet intervention on metabolic biomarkers in PLWH. [46] However, these studies have been conducted in predominately male, white cohorts.…”
Section: Other Factors Contribute To Insulin/glucose Metabolic Alteramentioning
confidence: 99%
“…They observed a positive association between kilocalories from sweets intake and higher insulin resistance as measured by the homeostatic model assessment of insulin resistance (HOMA-IR). [42] Investigations with self-reported dietary intake that evaluated the Mediterranean dietary pattern with biomarker profiles for diabetes and cardiovascular disease risk present equivocal results,[4345] while an upcoming study will directly measure the impact of a Mediterranean diet intervention on metabolic biomarkers in PLWH. [46] However, these studies have been conducted in predominately male, white cohorts.…”
Section: Other Factors Contribute To Insulin/glucose Metabolic Alteramentioning
confidence: 99%
“…In a cross-sectional study of 136 patients with at least 1 year of exposure to HAART, those individuals that reported moderate to high adherence to Mediterranean diet had lower frequency of lipodystrophy [51]. Another study showed that in lipodystrophic patients under HAART, adherence to Mediterranean diet was associated with lower insulin resistance (assessed by HOMA-IR), increased HDL cholesterol and reduced blood triglycerides levels [50]. Combined, these results suggest that Mediterranean diet may have protective effects on both HAART-induced lipodystrophy and its metabolic complications.…”
Section: Nutritional Interventions In the Management Of Lipodystrophymentioning
confidence: 99%
“…In addition, high consumption of carbohydrate (especially fructose) should also be avoided. The beneficial effect of a Mediterranean diet, enriched in n−3 polyunsaturated fatty acids (PUFAs), on metabolic parameters has been demonstrated in HIV-positive patients with highly active antiretroviral therapy (HAART)-induced metabolic syndrome [82]. Additional studies are warranted to determine whether this Mediterranean diet is equally effective in patients with inherited lipodystrophies.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%